Intra- and Inter-sample Variation in Wool Cortisol Concentrations of Australian Merino Lambs Between Twice or Single Shorn Ewes - Hantzopoulou, Georgia-Constantina; Sawyer, Gregory; Tilbrook, Alan; Narayan, Edward (Frontiers in Animal Science, 2022)
Stress in Merino sheep can cause a reduction in the quantity and quality of fine wool production. Furthermore, it has been found that environmental stress during pregnancy can negatively affect the wool follicles of the developing fetus. This study was part of a larger field investigation on the effects maternal shearing frequency on sheep reproductive and productivity outcomes. For this study, we investigated the intra- and inter- sample variation in wool cortisol levels of weaner lambs. We conducted two experiments, the first was to determine the intra- and inter- sample variation in wool samples taken from the topknot of weaned lambs, and the other aim was to determine any difference between maternal shearing treatment (single or twice shearing) on absolute wool cortisol levels of weaned lambs. In the first experiment, topknot wool was collected from 10 lambs, and each sample was further divided into 4 subsamples, leading to a total of 40 wool subsamples. For the second experiment, we collected the topknot from the 23 lambs produced by the shearing frequency treatment ewes (once or twice shorn). The samples were then extracted and analysed using a commercially available cortisol enzyme-immunoassay in order to determine the concentration of cortisol in each of the samples. Statistical analysis for the first experiment showed that there was no significant difference between the subsamples of each topknot wool sample taken from each lamb (p = 0.39), but there was a statistical difference between samples (p < 0.001), which was to be expected. In the second experiment, there was a significant difference between the lambs born to the one shearing and two shearing treatments (p = 0.033), with the lambs of the twice sheared ewes having higher average wool cortisol levels (2.304 ± 0.497 ng/g (SE); n = 14) than the ones born to once shorn ewes (1.188 ± 0.114 ng/g (SE), n = 8). This study confirms that the topknot wool sampling can be a reliable method adapted by researchers for wool hormonal studies in lambs. Second, ewes shorn mid-pregnancy gave birth to lambs with higher cortisol concentrations than ewes that remained unshorn during pregnancy.